العلاقة بين قلق المستقبل والتوافق النفسي لدى عينة من طلاب الصف الثاني الثانوي في محافظة ريف دمشق (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف البحث الحالي إلى الكشف عن العلاقة بين قلق المستقبل والتوافق النفسي لدى المراهقين, ودراسة الفروق بين الذكور والاناث في التعليم الثانوي العام بفرعيه العلمي والأدبي في متغيرات البحث(قلق المستقبل, التوافق النفسي)لدى عينة من طلبة الصف الثاني الثانوي.وقد تكوّن مجتمع البحث من مدارس التعليم الثانوي الحكومية في مدينة جرمانا, وهم طلبة الصف الثاني الثانوي(15- 17)سنة, وقد تم سحب العينة بشكل عشوائي والتي بلغت( 100) طالب وطالبة ومنقسمين (50 ذكور+ 50 اناث), واستخدمت الباحثة الأدوات التالية للدراسة: 1- مقياس قلق المستقبل من اعداد ناهد سعود, 2- مقياس التوافق النفسي اعداد جابر عبد الحميد جابر و يوسف محمود الشيخ, وقد اتبعت الباحثة المنهج الوصفي التحليلي وذلك لمناسبته لطبيعة البحث, وقد وضعت مجموعة من الفروض واختبرت صدقها, واتت النتائج كمايلي: (1) وجود علاقة دالة إحصائيا بين قلق المستقبل والتوافق النفسي لدى عينة البحث.(2) وجود فروق ذات دلالة إحصائية في قلق المستقبل تبعاً لمتغير الجنس لصالح عينة الإناث.(3) وجود فروق ذات دلالة إحصائية في قلق المستقبل تبعاً لمتغير التخصص الدراسي لصالح طلبة الفرع الأدبي. (4) لا توجد فروق ذات دلالة إحصائية في التوافق النفسي تبعاً لمتغير الجنس .(5) وجود فروق ذات دلالة إحصائية في التوافق النفسي تبعاً لمتغير التخصص الدراسي لصالح طلبة الفرع الأدبي, وفي ضوء هذه النتائج اقترحت الباحثة إجراء المزيد من الدراسات والبحوث حول مشكلات المراهقين والتعرف إليها في ضوء أوضاع مستجدات العالم, والعمل على تغيير أنظمة التقويم الباعثة على القلق والخوف لدى الطلاب, والسعي من اجل إيجاد فرص عمل تضمن للطالب أن يثابر دون إحساسه بالملل مما يدرسه. والعمل على إيجاد بيئة  صالحة مقبولة في المدرسة و المنزل تبعث على الرضا والسرور ممّا يؤدي إلى توافق نفسي سليم للمراهق, إضافة إلى توجيه الباحثين إلى الاهتمام بدراسة ظاهرة قلق المستقبل وآثاره النفسية على الحالة النفسية والاجتماعية للمراهق. This research aims to detect the relationship between future anxiety and psychological adjustment in adolescents, studies the differences between males and females in secondary education branches of general scientific and literary research variables (future anxiety, psychological adjustment) in a sample of (15-17) students in twelfth grade. The sample consisting of (100) students divided into (50 males +50 females) is randomly chosen. The researcher uses the following tools to study: 1 –  the future anxiety index prepared by (Nahed Saud), 2 – the crierion of psychological adjustment prepared by (Gaber Abdel-Hamid Jaber, Youssef Mahmoud al-Sheikh). The researcher follows the descriptive-analytical approach, developing a set of hypotheses, putting them to the test, coming up with the following results: (1) Statistically, there is a linking function between future anxiety and psychological adjustment in the research sample. (2) According to the gender variable for the females sample, there exist statistically significant differences in future anxiety. (3) the existence of statistically significant differences in future anxiety according to the specialty variable for students of the literary section. (4) There are no statistically significant differences in psychological adjustment depending on the gender variable. (5) the existence of statistically significant differences in psychological adjustment depending on the specialty variable for students of the literary section.  In the light of these findings, the researcher recommends further research on the problems facing adolescents, identifying them in the light of international developments, providing job opportunities for students to persevere their studies without ever feeling bored, finding a sound environment acceptable to school and house, creating a sense of satisfaction. Furthermore, researchers' attention should be directed towards studying the phenomenon of future anxiety and its psychological and social effects on teenagers.